Novel Insight of N6-Methyladenosine in Cardiovascular System - Huan Zhang; Wei Lu; Haoyue Tang; Aiqun Chen; Xiaofei Gao; Congfei Zhu; Junjie Zhang (Medicina)
N6-methyladenosine (m6A) is the most common and abundant internal co-transcriptional modification in eukaryotic RNAs. This modification is catalyzed by m6A methyltransferases, known as “writers”, including METTL3/14 and WTAP, and removed by demethylases, or “erasers”, such as FTO and ALKBH5. It is recognized by m6A-binding proteins, or “readers”, such as YTHDF1/2/3, YTHDC1/2, IGF2BP1/2/3, and HNRNPA2B1. Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality worldwide. Recent studies indicate that m6A RNA modification plays a critical role in both the physiological and pathological processes involved in the initiation and progression of CVDs. In this review, we will explore how m6A RNA methylation impacts both the normal and disease states of the cardiovascular system. Our focus will be on recent advancements in understanding the biological functions, molecular mechanisms, and regulatory factors of m6A RNA methylation, along with its downstream target genes in various CVDs, such as atherosclerosis, ischemic diseases, metabolic disorders, and heart failure. We propose that the m6A RNA methylation pathway holds promise as a potential therapeutic target in cardiovascular disease.